Consequences of Deregulation for Commercial Banking: Discussion - Eisenbeis, Robert A. (Journal of Finance, 1984)
Robert A. Eisenbeis, Consequences of Deregulation for Commercial Banking: Discussion, The Journal of Finance, Vol. 39, No. 3, Papers and Proceedings, Forty-Second Annual Meeting, American Finance Association, San Francisco, CA, December 28-30, 1983 (Jul., 1984), pp. 803-805